An Appendiceal Carcinoid Tumor within an Amyand’s Hernia Mimicking an Incarcerated Inguinal Hernia - Gregorios Christodoulidis; Konstantinos Perivoliotis; Alexandros Diamantis; Dionysios Dimas; Michael Spyridakis; Konstantinos Tepetes (Case Reports in Surgery)
Introduction. We report the case of an appendiceal carcinoid tumor within an Amyand’s hernia, presenting as an incarcerated right inguinal hernia. Presentation of Case. A 52-year-old male presented in the emergency department due to a persistent right inguinal pain. Clinical examination revealed a tender right groin mass. Laboratory tests revealed leukocytosis and an increased serum CRP. Under the diagnosis of an incarcerated right inguinal hernia, an emergency operation was taken. Intraoperatively, an inflamed appendix and a part of the cecum were found in the hernia sac. The operation was completed with an appendectomy and a modified Bassini hernia repair. Histological examination revealed a carcinoid tumor, resulting in the performance of a right hemicolectomy. Discussion. Amyand’s hernia is estimated to account for 0.4% to 0.6% of all inguinal hernias. Coexistence of an Amyand’s hernia and a neoplasia is quite rare. Carcinoids are the most frequent tumors found in the appendix, with the size of the primary tumor to be considered the most important prognostic factor and the basis upon which the operative plan is decided. Conclusion. A malignancy of the appendix should always be in the differential diagnosis of a right inguinal mass, in order to provide optimum surgical treatment.